2022
DOI: 10.3390/nu14020347
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte-to-HDL Ratio (MHR) Predicts Vitamin D Deficiency in Healthy and Metabolic Women: A Cross-Sectional Study in 1048 Subjects

Abstract: Vitamin D deficiency is often linked with Metabolic Syndrome, both being more frequent with ageing and associated with an increase inflammatory state. Recently, monocytes-to-high density lipoprotein (HDL) ratio (MHR) has emerged as a powerful index to predict systemic inflammation. In this cross-sectional study, we investigated the association between circulating vitamin D level (25-OH vitamin D) and inflammatory status in a population of 1048 adult individuals. Our study reveals an inverse association between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 54 publications
2
10
0
Order By: Relevance
“…We previously identified increased visceral adipose tissue and oxidative stress as predisposing conditions to impaired reverse cholesterol transport (RCT), a process in which HDL particles are critically involved ( 33 ). In this study, HDL level intriguingly shows significant correlations with FPG and WC only in subjects with benign nodules, while a significant direct correlation with 25-OH vitamin D, as previously reported ( 34 , 35 ), was found only in patients with malignant nodules. On the one hand, the paradoxical uncoupling of cholesterol bioavailability and synthesis has already been shown in cancer cells ( 36 ).…”
Section: Discussionsupporting
confidence: 87%
“…We previously identified increased visceral adipose tissue and oxidative stress as predisposing conditions to impaired reverse cholesterol transport (RCT), a process in which HDL particles are critically involved ( 33 ). In this study, HDL level intriguingly shows significant correlations with FPG and WC only in subjects with benign nodules, while a significant direct correlation with 25-OH vitamin D, as previously reported ( 34 , 35 ), was found only in patients with malignant nodules. On the one hand, the paradoxical uncoupling of cholesterol bioavailability and synthesis has already been shown in cancer cells ( 36 ).…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, Jiang et al found that MHR was significantly related to all-cause and cardiovascular mortality in the general population independent of established risk factors (9). De Matteis et al reported that MHR was independently correlated with vitamin D deficiency in healthy and metabolic women (29). All clinical findings indicated MHR can be a predictive marker for other kinds of chronic inflammatory disease like MetS.…”
Section: Discussionmentioning
confidence: 99%
“…De Matteis et al. reported that MHR was independently correlated with vitamin D deficiency in healthy and metabolic women ( 29 ). All clinical findings indicated MHR can be a predictive marker for other kinds of chronic inflammatory disease like MetS.…”
Section: Discussionmentioning
confidence: 99%
“…Low vitamin D levels have been linked to an increase in chronic low-grade inflammation through its direct action on different pro-inflammatory cytokines and chemokines released by macrophages [95]. Previous studies have reported that low levels of vitamin D correlate with increased MHR, independent of metabolic and age status [96,97]. These findings could be due to several mechanisms.…”
Section: Discussionmentioning
confidence: 99%